Pertimbangan Hakim dalam Penetapan Dispensasi Nikah di Pengadilan Agama Kraksaan - Imam Syafii (Al-Adillah: Jurnal Hukum Islam, 2021)
Marriage dispensation is legal assistance from the Religious Courts to prospective brides and grooms, one or both of whom have not reached the age requirement in the state regulations as stipulated in the Law. In the latest Marriage Law on Marriage, No. 16 of 2019 reads, "Marriage is only permitted if the man and woman have reached the age of 19" and the dispensation of marriage is discussed in paragraph (2) which reads, "In the event of deviation from the age requirement as referred to in paragraph (1), the parents men and women can ask for dispensation to the Court on the grounds that it is very urgent accompanied by sufficient supporting evidence ". The existence of the latest Law which is an amendment of the 1974 Marriage Law, the application for marriage dispensation is a problem, both for the applicant (prospective husband and wife) as well as for the Religious Courts or judges. From this, it is interesting to conduct research on how judges consider the decision of dispensation of marriage and the factors behind the application for marriage dispensation at the Kraksaan Religious Court in 2019. With this research, it is hoped that it can increase knowledge about judges' considerations in granting or rejecting dispensation requests and increase knowledge about the factors behind the submission of a marriage dispensation application so that it can be used as a basis for the next trial.